Procalcitonin prognostic value in predicting mortality among adult patients with sepsis due to Gram-negative bacteria (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Sepsis is a leading cause of mortality and morbidity globally. Gram-negative bacteremia was reported to have a high risk of septic shock and poor prognosis. This study aimed to evaluate the role of procalcitonin in predicting mortality in patients with sepsis due to Gram-negative bacteria. METHODS This was a retrospective cohort study performed based on medical records and sepsis registry of Tropical and Infectious Disease Division, Department of Internal Medicine, Cipto Mangunkusumo Hospital. The inclusion criteria were patients aged ≥18 years diagnosed with sepsis due to Gram-negative bacteria based on blood culture on admission and hospitalized between March 2017 and October 2020. Data taken from medical records included subjects’ characteristics, laboratory parameters, and 28-day mortality outcomes during hospitalization. Receiver operating characteristic was used to determine the area under the curve (AUC) of procalcitonin and its accuracy. RESULTS A total of 128 patients were eligible. The cumulative survival of patients with Gram-negative bacteremia was 48.4% (standard error 0.96%). The AUC of procalcitonin to predict mortality was 0.45 (95% confidence interval 0.36–0.54). Escherichia coli was the predominant microorganism in blood culture (n = 38, 29.7%). CONCLUSIONS Procalcitonin has a poor performance in predicting mortality of patients with sepsis due to Gram-negative bacteria.